2013
DOI: 10.1097/qad.0b013e32835bd1f0
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling activation and exhaustion of B cells in spontaneous controllers of HIV infection

Abstract: Objective To define the impact of chronic viremia and associated immune activation on B-cell exhaustion in HIV infection. Design Progressive HIV infection is marked by B-cell anergy and exhaustion coupled with dramatic hypergammaglobulinemia. Although both upregulation of CD95 and loss of CD21 have been used as markers of infection-associated B-cell dysfunction, little is known regarding the specific profiles of dysfunctional B cells and whether persistent viral replication and its associated immune activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 20 publications
(39 reference statements)
1
38
0
Order By: Relevance
“…Nevertheless, systemic accumulation of B-cells with CD27+CD21 low phenotype, e.g. during chronic viral infections, is also considered as a sign of aberrant B-cell activation and dysfunction within the memory compartment [21,30]. In this study we observed very similar B-cell changes in LN patients.…”
Section: Discussionsupporting
confidence: 77%
“…Nevertheless, systemic accumulation of B-cells with CD27+CD21 low phenotype, e.g. during chronic viral infections, is also considered as a sign of aberrant B-cell activation and dysfunction within the memory compartment [21,30]. In this study we observed very similar B-cell changes in LN patients.…”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, CD21 expression on previously CD21 þ B cells might become downregulated or silenced, indicating hyperactivated B cells. This cell type has been referred to as exhausted B cells because of its hypoproliferative behavior [42]. Similar findings were obtained in systemic lupus erythematosus (SLE) patients with abnormally low CD21 expression compared with healthy individuals [43].…”
Section: Discussionmentioning
confidence: 64%
“…Surprisingly, perturbation of global plasma IgG glycosylation was apparent even during acute infection, indicating that despite the long plasma half-life of IgG, infection rapidly impacts the composition, and therefore activity, of the antibody compartment. Furthermore, although elite controllers durably maintain HIV replication to undetectable levels and exhibit low-level systemic immune activation (23,24), the shift toward agalactosylated glycans was even more pronounced in these individuals compared with that in both treated and untreated chronically infected subjects ( Figure 1D), suggesting that unlike the T cell compartment, the B cell compartment in elite controllers is inflamed (25), resulting in the production of antibodies with altered glycan composition. However, despite this change, the increase in G0 could not explain the difference in ADCVI activity among infected subject groups.…”
Section: Antiviral Effector Activity Of Antibodies From Hiv-infected mentioning
confidence: 99%